Racial and Ethnic Disparities in Acute Myocarditis Outcomes in the United States - Maria F. Osorio; Paola Lecompte‐Osorio; Sebastian Vasquez‐Ariza; Michael Dangl; Louis Vincent; Johanna Contreras; Rosario Colombo (Clinical Cardiology, 2026)
ABSTRACT Background Racial and ethnic disparities in cardiovascular outcomes are well established, but whether these inequities extend to acute myocarditis remains insufficiently characterized. Hypothesis Racial and ethnic minority groups hospitalized with acute myocarditis would have higher odds of in‐hospital mortality than White patients. Methods Using the National Inpatient Sample from 2012 to 2021, we identified adult hospitalizations with a primary diagnosis of acute myocarditis. The primary outcome was all‐cause in‐hospital mortality. Secondary outcomes included cardiogenic shock, mechanical circulatory support (MCS), cardiac arrest, ventricular tachycardia/fibrillation (VT/VF), acute kidney injury, renal replacement therapy, and stroke. Multivariable logistic regression estimated adjusted odds ratios (aORs). Results A total of 105 235 weighted hospitalizations were identified. After adjustment, all minority groups had higher odds of in‐hospital mortality than White patients: Black (aOR 1.30, 95% CI 1.10–1.55), Hispanic (aOR 1.37, 95% CI 1.14–1.66), Asian/Pacific Islander (aOR 2.07, 95% CI 1.58–2.72), and Other (aOR 1.40, 95% CI 1.07–1.83). Asian/Pacific Islander patients had the highest odds of cardiogenic shock and MCS use. Black patients had higher odds of cardiac arrest and VT/VF. Hispanic patients had higher in‐hospital mortality despite lower odds of VT/VF and MCS use. Race and ethnicity by pandemic era interaction for mortality was not significant ( p = 0.072). Conclusions Among adults hospitalized with acute myocarditis, racial and ethnic minority groups had higher adjusted odds of in‐hospital mortality than White patients. Distinct patterns of complications further underscore the need for equitable, attentive, and risk‐informed clinical care.